THE EFFECT OF LISTENING TO MUROTTAL QUR'AN ON THE OXYGEN SATURATION LEVEL IN PRETERM INFANTS IN THE NEONATAL INTENSIVE CARE UNIT - Dina Sulviana Damayanti; Djauhar Ismail; Warsiti Warsiti (Belitung Nursing Journal, 2018)
Background: Preterm infants are at risk for respiratory and hypothermia disorders that may affect physiologic growth and development processes that can be aggravated by treatment processes while in the neonatal intensive care unit. Treatment in the NICU can trigger stress that can affect the vital signs and healing process of preterm infants, thus requiring non-medical treatment to stimulate the condition. This research provides a different treatment of sound therapy that has never been given to preterm infants in previous studies by listening murottal Al-Qur'an. Objective: To examine the effect of listening to the murottal Qur'an on oxygen saturation in preterm infants during treatment at the neonatal intensive care unit (NICU). Method: This was a pre-experimental study with one group pretest-posttest design from September to October 2017. The samples were 30 preterm infants treated at NICU of the General Hospital of Panembahan Senopati Bantul selected using accidental sampling. The analysis used was simple linear regression. Result: There was an increase of the oxygen saturation level after given intervention of Murottal Qur'an for 3 days. The first day of oxygen saturation intervention increased by 2.07%, the second day 3.75%, and the third day 4.65% compared to the oxygen saturation level before the intervention. Conclusion: Listening to murrotal Qur'an could statistically increase oxygen saturation, but clinically there was no significant change in preterm infants, as the increase of oxygen saturation level was still within normal limits.